2010
DOI: 10.1002/uog.8705
|View full text |Cite
|
Sign up to set email alerts
|

P28.14: Correlation between ultrasound diagnosis and autopsy findings of fetal malformations in second trimester terminations of pregnancy

Abstract: Specialist scan findings CCAML diaphragmatic hernia bright area in fetal heart ?echogenic focus ?rhabdomyoma cystic lesion in brain ?agenesis corpus collosum ?small left side heart large single atrium and ?AVSD CPCs, VSD and DORV Fetal medicine unit findings small CAM diaphragmatic hernia large apical VSD, dilated LV, dysplastic mv, small lvot cystic structure in brain not destroying tissue unlikely to have significant cardiac defect large atrial communication, tricuspid regurgitation not scanned Amniocentesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 0 publications
2
37
5
Order By: Relevance
“…the ability of USG in correctly diagnosing each malformation) ranges from 93% to 99%. [14] In our study, the sensitivity was 47.05% and specificity 45.45% which is much lower than the previous study. We have true positivity of 35.5% and true negativity of 11.1%.…”
Section: Discussioncontrasting
confidence: 50%
“…the ability of USG in correctly diagnosing each malformation) ranges from 93% to 99%. [14] In our study, the sensitivity was 47.05% and specificity 45.45% which is much lower than the previous study. We have true positivity of 35.5% and true negativity of 11.1%.…”
Section: Discussioncontrasting
confidence: 50%
“…Throughout the 30‐year period, a small group of fetal medicine experts have been responsible for most of the ultrasound examinations at the center. As found in other studies, ultrasound examinations performed at tertiary centers were more accurate than examinations performed in non‐specialized departments. Additionally, our policy has been to search for all anomalies present, including in cases in which a dominant serious finding leads to the decision to terminate a pregnancy.…”
Section: Discussionmentioning
confidence: 84%
“…The results of recent studies comparing prenatal US and autopsy findings are shown in Table . There is complete agreement of autopsy and US findings in 46% to 91% of cases.…”
Section: Discussionmentioning
confidence: 99%